Transverse V-Y advancement composite tissue flap for repairing defects after longitudinal melanonychia excision—a retrospective cohort study - Zhang, Jianhua; Xie, Zhenjun; Su, Wei (Frontiers in Surgery, 2025)
Longitudinal melanonychia (LM) is a common nail disorder that sometimes requires surgical excision to rule out malignancy. However, longitudinal complete removal of LM, as one type of method for some special patient, can leave a significant defect in the nail bed. We introduced and assessed the application of transverse V-Y advancement composite tissue flap, a novel surgical procedure designed to address these defects. From September 2017 to January 2024, a total of 17 patients with LM underwent complete excision of the affected nail bed. The tissue defects ranged from 3 to 8 mm in width. The wounds were repaired using the transverse V-Y advancement composite tissue flap, which included the nail, nail fold, and adjacent finger pulp skin. All patients were followed up to assess flap survival, nail regrowth, and functional outcomes, and the mean follow-up time was 14 months, with a range of 6–23 months. All 17 flaps survived without complications. Nail regrowth was satisfactory in 15 cases, with only 2 cases showing a slight longitudinal ridge. Sensory recovery was well in all patients. Recurrence of LM was observed in 1 case (5.9%) during the follow-up period. The transverse V-Y advancement composite tissue flap is a reliable and effective alternative for repairing defects after LM complete excision identified as the indicating lesion, particularly for defects ranging from 3 to 8 mm in width. This technique significantly improves both functional and cosmetic outcomes, with high patient satisfaction.